the roots of +bx+c=0 ate in ratio m:n
let the roots be mk and nk respectively
=>a +bmk+c=0
=>a +bmk+c=0.....(1)
Similarly,
a +bnk+c=0......(2)
(1)-(2)
=>a(-)+bk(m-n)=0
=>a(m+n)(m-n)+bk(m-n)=0
=>k(m-n)(ak(m+n)+b)=0
=>ak(m+n)+b=0
=>ak(m+n)=-b
=>k=-
therefore,
the roots are mk=-
(or)
nk=-
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
After letting one root be mk and other be nk.
You could have directly used sum of roots = a−b
∴k=a(m+n)−b
Roots are,
a(m+n)−mb and a(m+n)−nb